Study on the improvement of behavior and pain and the mechanism of Yangpafang in subacute Parkinson's disease model mice - SHI Ying; MEI Shan‐shan; WANG Yuan‐ling; XIA A‐long; WANG Xiao‐wei; LI Jun (Chinese Journal of Contemporary Neurology and Neurosurgery)
Objective Explore the therapeutic effect of Yangpafang on behavior and pain in subacute Parkinson's disease (PD) model mice and its possible mechanism. Methods Total 42 specific pathogen⁃free (SPF) C57BL/6J mice were randomly divided into control group, model group, Yangpafang low⁃ dose group [13.50 g/(kg·d)], medium ⁃dose group [40.50 g/(kg·d)] and high⁃dose group [121.50 g/(kg·d)], levodopa and benserazide group (7 mice in each group). The behavioral changes of mice were evaluated by Pole Climbing Test, Suspension Test and Field Test. The thermal nociceptive threshold and mechanical nociceptive threshold were measured by thermal pain response latency measuring instrument and electronic pressure pain measuring instrument. Immunohistochemical staining was used to detect the positive expression of tyrosine hydroxylase (TH) in substantia nigra and amygdala. Results There were significant differences in pole climbing time (F = 14.625, P = 0.000), suspension score (F = 24.493, P = 0.000), resting time of Field Test (F = 24.506, P = 0.000), thermal nociceptive threshold (F = 24.726, P = 0.000) and mechanical nociceptive threshold (F = 21.052, P = 0.000), TH positive expression in substantia nigra (F = 19.663, P = 0.000) and amygdala (F = 36.513, P = 0.000) among different treatment groups. Compared with the control group, the pole climbing time (P = 0.000) and resting time (P = 0.000) of the model group were prolonged, and the suspension score (P = 0.000), thermal nociceptive threshold (P = 0.000) and mechanical nociceptive threshold (P = 0.000), substantia nigra (P = 0.000) and amygdala (P = 0.000) TH positive expression decreased. Compared with the model group, the pole climbing time (P = 0.020, 0.000, 0.000, 0.000) and resting time (P = 0.000, 0.000, 0.000, 0.000) of Yangpafang low⁃dose group, medium⁃dose group, high ⁃ dose group and levodopa and benserazide group were shortened, but still longer than those of the control group (P < 0.05, for all). The suspension score (P = 0.000, 0.000, 0.000, 0.000, 0.000), thermal nociceptive threshold (P = 0.008, 0.000, 0.000, 0.000) and mechanical nociceptive threshold (P = 0.003, 0.000, 0.000, 0.000), TH positive expression in substantia nigra (P = 0.031, 0.001, 0.000, 0.000) and amygdala (P = 0.007, 0.000, 0.000, 0.000) increased. The thermal nociceptive threshold in other 3 groups was still lower than that in the control group (P < 0.05, for all), except that the levodopa and benserazide group returned to the level of the control group (P = 0.063). Compared with the Yangpafang low⁃dose group, the pole climbing time (P = 0.009, 0.009, 0.006) and resting time (P = 0.024, 0.018, 0.001) in the Yangpafang medium ⁃ dose group, high ⁃ dose group and the levodopa and benserazide group were also shortened, but still longer than those in the control group (P < 0.05, for all). Suspension score (P = 0.015, 0.011, 0.002), thermal nociceptive threshold (P = 0.001, 0.001, 0.000) and mechanical nociceptive threshold (P = 0.035, 0.001, 0.001) also increased, TH positive expression was also increased in the substantia nigra (P = 0.043, 0.023, 0.001) and amygdala (P = 0.007, 0.005, 0.000). Except that the TH positive expression in the amygdala of the levodopa and benserazide group was higher than that of the Yangpafang medium⁃dose group (P = 0.009) and the high⁃dose group (P = 0.012), there was no significant difference in each index between the latter 3 groups (P > 0.05, for all). Conclusions Yangpafang can improve the behavior and pain of subacute PD model mice, which is related to the protection of amygdala and substantia nigra dopaminergic neurons.